219k views
5 votes
A, B, and C are polynomials, where: A = 3x – 4 B = x + 7 C = x2 + 2 What is A2 – (B + C) in simplest form? 8x2 – 25x + 7 8x2– 25x + 11 10x2 – 25x + 7 10x2 – 25x + 11

User Migdsb
by
5.4k points

2 Answers

5 votes

Answer:

A

Explanation:

I took the assignment on Ed gen uity

User Jonck
by
5.0k points
2 votes

Answer:

8x²-25x+7......

Explanation:

A² = (3x-4)(3x-4)

A² = 3x(3x-4) - 4(3x-4)

A² = 9x² - 12x - 12x + 16

A² = 9x² - 24x + 16

while

B+C = (x+7) + (x² +2)

B+C = x+7+x²+2

B+C = x²+x+9

Therefore:

A² - (B+C) = 9x² - 24x + 16 - (x²+x+9)

= 9x² - 24x + 16 - x² - x - 9

= 8x²-25x+7

User GuidoMB
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.